2006
DOI: 10.1111/j.1468-2982.2005.00998.x
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Study of Headache in Florianopolis, Brazil

Abstract: The aim of this study was to estimate the 1-year prevalence of headache, migraine, tension-type headache (TTH) and chronic daily headache (CDH), and the degree of association of migraine with some sociodemographic characteristics of the population of Florianopolis, Brazil. This is a cross-sectional, door-to-door, population-based study. In 300 randomly selected households, 625 subjects, aged 15-64 years, responded to a structured questionnaire. The 1-year prevalence of headache was 80.8%, of migraine 22.1%, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
95
5
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(137 citation statements)
references
References 43 publications
26
95
5
11
Order By: Relevance
“…Another factor confirmed by this study was the higher prevalence of headache among women, which has also been found in other studies 1,4,5 in which pain is often associated with emotional or hormonal triggering factors. Also related to the fact of being women, the use of oral contraceptive or the presence of regular menstruation were not associated with the incidence of headaches as described in the literature 4,23,24 .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Another factor confirmed by this study was the higher prevalence of headache among women, which has also been found in other studies 1,4,5 in which pain is often associated with emotional or hormonal triggering factors. Also related to the fact of being women, the use of oral contraceptive or the presence of regular menstruation were not associated with the incidence of headaches as described in the literature 4,23,24 .…”
Section: Discussionsupporting
confidence: 90%
“…The results showed a high prevalence of headaches in the population studied, which corroborates other studies developed in the country 4,5,22 , in which prevalence rates ranged from 48.1 percent to 80.8 percent.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations